2000
DOI: 10.1034/j.1399-3003.2000.16a26.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 in stable bronchiectasis

Abstract: Endothelin (ET)-1 has been suggested to promote neutrophil adhesion to endothelium, migration to inflamed areas, and release of elastase. ET-1 might therefore play a role in the pathogenesis of bronchiectasis, a chronic inflammatory and infective airway disease which is still poorly understood.Thirty five patients with stable bronchiectasis (20 females, mean age SD 49.1 15.0 yrs) and 18 control subjects (8 females, 49.4 11.3 yrs) were recruited prospectively. The ET-1 levels in serum and sputum were measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
0
19
0
1
Order By: Relevance
“…Sputum ET-1 levels are increased in patients with cystic fibrosis [59], and sputum ET-1 correlated with Pseduomonas infection in noncystic fibrosis related bronchiectasis [70]. …”
Section: Airway Diseasesmentioning
confidence: 99%
“…Sputum ET-1 levels are increased in patients with cystic fibrosis [59], and sputum ET-1 correlated with Pseduomonas infection in noncystic fibrosis related bronchiectasis [70]. …”
Section: Airway Diseasesmentioning
confidence: 99%
“…Previous studies have shown the presence of intense inflammatory activity characterized by neutrophils, T-cells and interleukin (IL)-8 positive cells and elevated levels of IL-6, IL-8, tumour necrosis factor (TNF)-α, leukotriene B4, endothelin 1, elestase in sputum and bronchoalveolar lavage samples of bronchiectasis patients (7)(8)(9)(10)(11)(12). Recent evidence suggests the presence of systemic inflammation in chronic inflammatory airway diseases.…”
Section: Does Airway Colonization Cause Systemic Inflammation In Bronmentioning
confidence: 99%
“…Macrophages contribute to neutrophil influx into the airways via the production of TNF-a [75] and endothelin (ET)-1 [113]. They also function as regulatory cells, releasing a number of inflammatory mediators, including TNF-a, IL-8, other CXC chemokines, monocyte chemotactic peptide 1, LTB 4 , ROS and a number of elastolytic enzymes [95,114,115].…”
Section: Macrophagesmentioning
confidence: 99%
“…Human airway epithelial cells produce ET-1, which promotes neutrophil adhesion to endothelial cells, migration to areas of inflammation and the release of elastase in vitro [113].…”
Section: Epithelial Cellsmentioning
confidence: 99%